A Natural Compound Mixture Containing Arctigenin, Hederagenin, and Baicalein Alleviates Atopic Dermatitis in Mice by Regulating HPA Axis and Immune Activity. (29th June 2020) - Nguyen, Ly Thi Huong; Oh, Tae-Woo; Nguyen, Uy Thai; Choi, Min-Jin; Yang, In-Jun; Shin, Heung-Mook
Abstract : Forsythiae Fructus, Lonicerae Flos, and Scutellariae Radix are medicinal herbs that possess anti-inflammatory and anti-atopic effects. Hence, we investigated the effects of a mixture (ADM), containing arctigenin, hederagenin, and baicalein, which are the main compound from these herbs on atopic dermatitis (AD) skin lesions and the underlying molecular mechanisms. ADM was topically applied to dorsal skin lesions of 2, 4-dinitrochlorobenzene- (DNCB-) induced ICR mice, and the expressions of proinflammatory mediators and HPA axis hormones were investigated. The topical application of 0.5% ADM significantly reduced the DNCB-induced symptoms of AD in ICR mice. Histological analysis showed that ADM exerted antiatopic effects by reducing the epidermal thickness and mast cell infiltration into skin lesions. 0.5% ADM attenuated the levels of TNF- α, IFN- γ, IL-4, and VEGF in skin lesions and serum IgE. The production of Th1-/Th2-related cytokines in splenic tissues, including TNF- α, IFN- γ, IL-12, and IL-4, were also decreased by ADM treatment. ADM diminished corticotropin-releasing hormone (CRH), adrenocorticotropic hormone (ACTH), and corticosteroid (CORT) production in DNCB-induced mice. In vitro, ADM reduced the productions of TARC/CCL17, MDC/CCL22, IL-6, and ICAM-1 in TNF- α /IFN- γ - (TI-) stimulated HaCaT cells by suppressing the ERK and JNK signaling pathways. In addition, ADM inhibited corticotropin-releasing hormone/substance P- (CRH/SP-) induced VEGF production in HMC-1 cells. These results suggest that ADM may have therapeutic potential in AD by reducing inflammation and attenuating HPA axis activation.